Assessment of Bona Fide sRNAs in Staphylococcus aureus - Liu, Wenfeng; Rochat, Tatiana; Toffano-Nioche, Claire; Le Lam, Thao Nguyen; Bouloc, Philippe; Morvan, Claire (Frontiers in Microbiology, 2018)
Bacterial regulatory RNAs have been extensively studied for over a decade, and are progressively being integrated into the complex genetic regulatory network. Transcriptomic arrays, recent deep-sequencing data and bioinformatics suggest that bacterial genomes produce hundreds of regulatory RNAs. However, while some have been authenticated, the existence of the others varies according to strains and growth conditions, and their detection fluctuates with the methodologies used for data acquisition and interpretation. For example, several small RNAs (sRNA) candidates are now known to be parts of UTR transcripts. Accurate annotation of regulatory RNAs is a complex task essential for molecular and functional studies. We defined bona fide sRNA as those that i) likely act in trans and ii) are not expressed from the opposite strand of a coding gene. Using published data and our own RNA-seq data, we reviewed hundreds of Staphylococcus aureus putative regulatory RNAs using the DETR’PROK computational pipeline and visual inspection of expression data, addressing the question of which transcriptional signals correspond to sRNAs. We conclude that the model strain HG003, a NCTC8325 derivative commonly used for S. aureus genetic regulation studies, has only about 50 bona fide sRNAs, indicating that these RNAs are less numerous than commonly stated. Among them, about half are associated to the S. aureus sp. core genome and a quarter are possibly expressed in other Staphylococci. We hypothesize on their features and regulation using bioinformatic approaches.